Pain-related nucleus accumbens function: modulation by reward and sleep disruption. Issue 5 (May 2019) - Seminowicz, David A.; Remeniuk, Bethany; Krimmel, Samuel R.; Smith, Michael T.; Barrett, Frederick S.; Wulff, Andreas B.; Furman, Andrew J.; Geuter, Stephan; Lindquist, Martin A.; Irwin, Michael R.; Finan, Patrick H.
Abstract : Abstract: The nucleus accumbens (NAc) has been implicated in sleep, reward, and pain modulation, but the relationship between these functional roles is unclear. This study aimed to determine whether NAc function at the onset and offset of a noxious thermal stimulus is enhanced by rewarding music, and whether that effect is reversed by experimental sleep disruption. Twenty-one healthy subjects underwent functional magnetic resonance imaging scans on 2 separate days after both uninterrupted sleep and experimental sleep disruption. During functional magnetic resonance imaging scans, participants experienced noxious stimulation while listening to individualized rewarding or neutral music. Behavioral results revealed that rewarding music significantly reduced pain intensity compared with neutral music, and disrupted sleep was associated with decreased pain intensity in the context of listening to music. In whole-brain family-wise error cluster-corrected analysis, the NAc was activated at pain onset, but not during tonic pain or at pain offset. Sleep disruption attenuated NAc activation at pain onset and during tonic pain. Rewarding music altered NAc connectivity with key nodes of the corticostriatal circuits during pain onset. Sleep disruption increased reward-related connectivity between the NAc and the anterior midcingulate cortex at pain onset. This study thus indicates that experimental sleep disruption modulates NAc function during the onset of pain in a manner that may be conditional on the presence of competing reward-related stimuli. These findings point to potential mechanisms for the interaction between sleep, reward, and pain, and suggest that sleep disruption affects both the detection and processing of aversive stimuli that may have important implications for chronic pain. Abstract : Supplemental Digital Content is Available in the Text.This study contributes to our understanding of mechanisms supporting the association of sleep, reward, and pain by showing that sleep disruption attenuates nucleus accumbens activation during pain onset, and increases connectivity with the anterior midcingulate cortex when rewarding and noxious stimuli are presented at the same time.